Relocating earthquakes by hypodd in Cınarcık basın and surrounding - Bulut, Fatih. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2005., 2006)
We relocated part of aftershock activity in <;marclk Basin and surrounding that are associated with the 1999 izmit Earthquake Mw 7.4. We used double difference relocation algorithm (Waldhauser and Ellsworth, 2000) to relocate the aftershocks. The data set was obtained by a temporary seismic network deployed by Bogazi9i University, Kandilli Observatory and Earthquake Research Institute, LGIT (Grenoble) and IPGP (Paris) 10 days after the mainshock (Karabulut et al., 2002). For a better station coverage, additional data set was obtained from a network operated by TUBITAK Marmara Research Center. Differential travel times were calculated using both arrival time readings and waveform cross correlation method. We relocated 1550 of the aftershocks and interpreted the results by classification into three main clusters, namely, Tuzla, Y alova and Central Cluster. Tuzla Cluster is located in the northern scarp of the <;marclk Basin and shows events that are linearly oriented in NW-SE direction. The depth section of this cluster indicates a vertically dipping activity,. The linear trend might imply a secondary strike-slip faulting parallel to the main one. However, the earlier fault plane solutions do not confirm this statement. Y alova Cluster contains a well-developed aftershock activity that is located beneath the north of the Armutlu Peninsula. The depth section of this activity reveals a well defined linearly dipping characteristic which is plunging to the Iiorth with an approximate angle of 56°. The orientation of the seismicity is roughly EW and therefore parallel to the main rupture of 1999 izmit Earthquake. The Central Cluster traverses the total length of the Gulf of izmit and extends into the <;marctk Basin linearly with the orientation of E-W direction. It corresponds to the continuation of the main rupture of 1999 Izmit Earthquake to the west of the Hersek Peninsula. The relocation results obtained by HypoDD reveal seismicity patterns in a more clarified manner, provide more convincing data for models that were proposed before and fmally imply new seismological ideas about the Eastern Marmara.
Keywords: Earthquakes -- Turkey -- Çınarcık.; Seismology -- Data processing.